VD_FINDINFO Jug / 2019 / 423 vom 13. September 2019 - VD Tribunal cantonal (2019)
JUGE UNIQUE, DISPOSITIONS PÉNALES DE LA LCR, FENÊTRE{ÉQUIPEMENT DU VÉHICULE}, CONTRAVENTION, ÉTAT DÉFECTUEUX DU VÉHICULE | 93 al. 2 let. a LCR, 57 al. 2 OCR, 71a al. 4 OETV, 398 al. 4 CPP (CH), 406 al. 1 let. c CPP (CH)